Comparison of ventilatory and blood lactate thresholds in elite soccer players - Parpa, K.; Michaelides, M. (SportMont, 2022)
Despite a long research history, the lactate threshold continues to be a widely controversial field. Notwithstanding the controversies and influence of multiple determinants, the estimation of lactate threshold in sports has been considered one of the essential parameters in the prescription of training intensity, load monitoring, and performance prediction. The study aimed to compare the anaerobic ventilatory and lactate thresholds as determined by different methods in elite soccer players. The study consisted of twenty-five division 1 elite soccer players. The players were separated into two groups based on their run times on the treadmill. Group 1 (age 24.38±7.33 years, height 180.33±7.03 cm, weight 75.53±7.68 kg) consisted of players who completed more than 17 minutes on the treadmill, while group 2 (age 25.11±6.07 years, height 182.11±10.03 cm, weight 79.72±7.54 kg) consisted of those who completed less than 17 minutes. The players completed an incremental maximal cardiopulmonary exercise testing from which ventilatory thresholds were determined. Furthermore, measurements of blood samples were obtained every 3 minutes after completing each stage of the test, with a total of 141 measurements completed. Multivariate tests indicated no significant differences in the speeds calculated with ventilatory and lactate threshold methods. These findings suggest that the anaerobic ventilatory threshold (VT2) can be used as an alternative to the invasive lactate threshold measurements. Therefore, identifying a threshold point without utilizing an inva- sive procedure enhances the potential application of the VT2 or respiratory compensation point.